2021
DOI: 10.1155/2021/9923112
|View full text |Cite
|
Sign up to set email alerts
|

LSTMCNNsucc: A Bidirectional LSTM and CNN-Based Deep Learning Method for Predicting Lysine Succinylation Sites

Abstract: Lysine succinylation is a typical protein post-translational modification and plays a crucial role of regulation in the cellular process. Identifying succinylation sites is fundamental to explore its functions. Although many computational methods were developed to deal with this challenge, few considered semantic relationship between residues. We combined long short-term memory (LSTM) and convolutional neural network (CNN) into a deep learning method for predicting succinylation site. The proposed method obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…However, when the window size was greater than 33, the AUC tended to decrease. The results demonstrated that short peptides would miss vital information, and long peptides would include noise or redundancies (G. Huang et al, 2021). To verify the rationality of the results, two‐sample Logos (Vacic et al, 2006) was used to analyze the differences between positive and negative samples with 33 residues (Figure S3 of the Supporting Information Material).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the window size was greater than 33, the AUC tended to decrease. The results demonstrated that short peptides would miss vital information, and long peptides would include noise or redundancies (G. Huang et al, 2021). To verify the rationality of the results, two‐sample Logos (Vacic et al, 2006) was used to analyze the differences between positive and negative samples with 33 residues (Figure S3 of the Supporting Information Material).…”
Section: Resultsmentioning
confidence: 99%
“…Combining CNN and LSTM compensates for information loss, which allows the acquisition of multiangle features and more promising results (Guo et al, 2019;. G. Huang et al (2021) proposed a CNN-LSTM model and verified its feasibility. However, CNN and LSTM still have several deficiencies.…”
Section: Introductionmentioning
confidence: 98%
“…In addition to those discussed, deep learning can also be applied for other PTMs’ predictions, including methylation [110] , S-nitrosylation [111] , succinylation [112] , [113] , malonylation [114] , [115] , S-sulphenylation [116] , [117] , crotonylation [118] , [119] , [120] , [121] , 2- hydroxyisobutyrylation [122] , glutarylation [123] , N-palmitoylation [124] carbonylation [125] , and SUMOylation [126] . In particular, crotonylation prediction has demonstrated highly accurate results based on deep-learning methods.…”
Section: Other Ptmsmentioning
confidence: 99%
“…In the same year, Thapa et al developed DeepSuccinylSite which used deep learning methods to identify succinylation sites through embedding and a thermal encoding ( Thapa et al, 2020 ). In 2021, Huang et al combined a long short-term memory (LSTM) and convolutional neural network (CNN) into a deep learning method for predicting lysine succinylation sites ( Huang et al, 2021 ). Although existing deep learning-based methods can effectively predict the succinylation sites, most of them suffer from the time-consuming training process because of a number of hyperparameters and complicated structures.…”
Section: Introductionmentioning
confidence: 99%